Penerapan Digital Entrepreneurship bagi Pelaku UMKM di Pulau Pasaran Kelurahan Kotakarang Kota Bandar Lampung: Penelitian - Neli Aida; Sandi Asmara; Kamadie Sumanda Syafis; Resha Moniyana; Fatkhur Rohman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aimed to improve the competency of Micro, Small, and Medium Enterprises (MSMEs) in Pulau Pasaran Village, Kotakarang Subdistrict, Bandar Lampung City, in adopting the concept of digital entrepreneurship. The focus of the activities included the use of the QRIS-based payment platform and the use of the APiK application to assist in the preparation of financial reports. The program was implemented through a series of training, intensive mentoring, and live simulations designed to provide practical experience to participants. The results of these activities showed that MSMEs can utilize QRIS to support digital transactions and expand access to a wider market. In addition, the APiK application had been proven to simplify the process of recording and reporting business finances. The positive impact of this program was seen in increased digital literacy and better financial management among MSMEs. This program is expected to continue to encourage the digital transformation of MSMEs and strengthen the local economy.